Abba's child eaudiobook The cry of the heart for intimate belonging. - Manning, Brennan (christianaudio, 2005)
Many Christians have bought into the lie that we are worthy of God's love only when our lives are going well. If our families are happy or our jobs are meaningful, life is a success. // Yet when life begins to fall apart and embarrassing sins threaten to reveal our less-than-perfect identity, we scramble to keep up a good front to present to the world-and to God. We cower and hide until we can rearrange the mask of perfection and look good again. Sadly, it is then that we wonder why we lack intimate relationships and a passionate faith. // All this time, though, God is calling us to take our masks off and come openly to Him. God longs for us to know in the depths of our beings that He loves us and accepts us as we are. When we are our true selves, we can finally claim our identity as God's children and experience His pure pleasure in who we are. Brennan Manning encourages us to let go of the impostor lifestyle and freely accept our belovedness as a child of the heavenly Father. In Him there is life, our passion is rekindled, and our union with Him is His greatest pleasure.